Expression of dual-specificity phosphatase 5 pseudogene 1 (DUSP5P1) in tumor cells. - Martin S Staege; Katja Müller; Stefanie Kewitz; Ines Volkmer; Christine Mauz-Körholz; Toralf Bernig; Dieter Körholz (PLoS ONE, 2014)
Sequencing of individual clones from a newly established cDNA library from the chemoresistant Hodgkin's lymphoma cell line L-1236 led to the isolation of a cDNA clone corresponding to a short sequence from chromosome 1. Reverse transcriptase-polymerase chain reaction indicated high expression of this sequence in Hodgkin's lymphoma derived cell lines but not in normal blood cells. Further characterization of this sequence and the surrounding genomic DNA revealed that this sequence is part of a human endogenous retrovirus locus. The sequence of this endogenous retrovirus is interrupted by a pseudogene of the dual specificity phosphatase 5 (DUSP5). Reverse transcriptase-polymerase chain reaction revealed high expression of this pseudogene (DUSP5P1) in HL cell lines but not in normal blood cells or Epstein-Barr virus-immortalized B cells. Cells from other tumor types (Burkitt's lymphoma, leukemia, neuroblastoma, Ewing sarcoma) also showed a higher DUSP5P1/DUSP5 ratio than normal cells. Furthermore, we observed that higher expression of DUSP5 in relation to DUSP5P1 correlated with the expression of the pro-apoptotic factor B cell leukemia/lymphoma 2-like 11 (BCL2L11) in peripheral blood cells and HL cells. Knock-down of DUSP5 in HL cells resulted in down-regulation of BCL2L11. Thus, the DUSP5/DUSP5P1 system could be responsible for regulation of BCL2L11 leading to inhibition of apoptosis in these tumor cells.